Cladribine tablets as therapy for advanced relapsing-remitting multiple sclerosis: a 4-year follow-up real-world, multi-center, retrospective, cohort study - Pogoda-Wesołowska, Aleksandra; Stępień, Adam; Wnuk, Marcin; Marona, Monika; Tokarz-Kupczyk, Elżbieta; Piasecka-Stryczyńska, Karolina; Rejdak, Konrad; Jamroz-Wiśniewska, Anna; Adamczyk-Sowa, Monika; Kubicka-Bączyk, Katarzyna; Kurkowska-Jastrzębska, Iwona; Kurowska, Katarzyna; et al. (Frontiers in Neurology, 2025)
IntroductionCladribine tablets (CladT) are a high-efficacy disease-modifying therapy recommended for the treatment of relapsing–remitting multiple sclerosis (RRMS) particularly in early disease. This study is aimed to evaluate the long-term efficacy of CladT in population of Polish RRMS patients, with more advanced disease.MethodsThis retrospective observational study included patients with RRMS who started CladT treatment between December 2019 and November 2023. Collected data included prior treatments, annualized relapse rate (ARR), magnetic resonance imaging (MRI) activity, Expanded Disability Status Scale (EDSS) score, no evidence of disease activity (NEDA-3), lymphocyte counts, and safety outcomes were collected.ResultsOf the 230 patients (8.3% treatment-naïve, mean disease duration 9.2 years), follow-up data were available up to year 1 for 222 patients, year 2 for 154 patients, year 3 for 87 patients and year 4 for 31 patients. The ARR decreased from 1.42 at baseline to 0.26, 0.22, and 0.36 in years 1, 2, and 3, respectively. The proportion of relapse-free patients increased from 13.9% at baseline to 76.8% in year 1, 82% in year 2 and 75.4% in year 3 with no relapses reported in year 4. The proportion of patients with active MRI lesions declined from 90.4% at baseline to 36.3% in year 1, 25.2% in year 2, 45.9% in year 3 and 8.3% in year 4. Stable or improved EDSS was observed in 85.9% of patients in year 1, 80.8% in year 2, 73.7% in year 3 and 88.9% in year 4. NEDA-3 status was achieved in 47.4% of patients in year 1, 51.0% in year 2, 40.4% in year 3 and 71.4% in year 4. Adverse events were reported in 16.7% of patients in years 1–2 and in 6.3% of patients in year 3.DiscussionThe results indicate that CladT is effective and safe in Polish patients with RRMS, characterized by high disease activity, delayed treatment initiation, and multiple number of prior therapies.